Predictors of Mental Health Help Seeking Among Cambodian Adolescents - Khann, Sareth; Minh, Dang Hoang; Weiss, Bahr (VNU Journal of Science: Education Research, 2019)
Mental health problems are a major global burden. Understanding what motivates people to seek help for mental health problems thus is important so society can best support people in help-seeking. The present study investigated predictors of mental health help-seeking among Cambodian adolescents. Participants were 391 Cambodian high-school students, assessed on (a) culturally-specific mental health syndromes ( Culturally-Specific Syndrome Inventory ); (b) depression ( PHQ-9 ); (c) anxiety ( GAD-7 ); (d) functional impairment ( Brief Impairment Scale ); (e) quality of life ( Q-LES-Q-SF ); and (f) help-seeking from different sources (e.g., friends, psychologists) ( General Help-Seeking Questionnaire).   Help seeking from mental health professionals was predicted by mental health symptoms but not by life impairment or quality of life, suggesting that these constructs are not understood as part of adolescent mental health in Cambodia. However, informal support was predicted by impairment and quality of life, suggesting that Cambodian adolescents are aware of life impairment and quality of life, desire to improve their lives, but are unaware of these constructs’ connection to mental health. Results suggest areas for public health campaigns in Cambodia to target to increase adolescent mental health support seeking. Results also suggest it may be useful to develop informal online mental health support resources for Cambodian adolescents.